Endoscopic Study of Ethmoidal Canals in Cadavers, Including a Histological Analysis of Their Contents - Felippu, Alexandre Wady Debes; Morsch, Thiago Picolli; Felippu, André Wady Debes; Cascio, Filippo; Oliveira, Claudia Regina Gomes Cardim Mendes de; Felippu, Alexandre; Voegels, Richard Louis (International Archives of Otorhinolaryngology, 2023)
Introduction The advent of the endoscope has enabled the use of the endonasal approach for a variety of diseases. Studying the ethmoidal canals is important for surgeries of the paranasal sinuses and the anterior base of the skull.Objective To investigate the ethmoidal canals and evaluate their structure, the presence of vessels and nerves, their location, and to perform an anatomopathological study of their contents.Methods We evaluated 20 cadavers (20 left and 20 right nasal cavities) through endoscopic dissection of the anterior base of the skull and exposure of the medial periorbita and dura mater; then, the ethmoidal canals were located and measured in relation to the anterior wall of the sphenoid sinus and between the ethmoidal canals, followed by removal of their content for histological analysis.Results Vessels were present in 75% of the left anterior ethmoidal canals, 70% of the left posterior ethmoidal canals, 75% of the left middle ethmoidal canals, 85% of the right anterior ethmoid canals, and 64.5% of the right posterior ethmoid canals; 50% of the right middle ethmoidal canals contained one vessel.Conclusion The ethmoidal canal does not necessarily contain an ethmoidal artery. Studies with a larger sample should be performed to quantify the correct proportion of arteries and ethmoidal canals.
Keywords: ethmoid sinus; ophthalmic artery; dissection; ethmoid bone; skull base